Volumetric Measurement of Vestibular Schwannoma Tumour Growth Following Partial Resection: Predictors for Recurrence - Vakilian, Siavosh; Souhami, Luis; Melançon, Denis; Zeitouni, Anthony (Journal of Neurological Surgery Part B: Skull Base, 2012)
Vestibular schwannomas (VS) have a higher risk of recurrence following subtotal resection than following near-total resection. We measured tumor remnant growth volumetrically in an attempt to determine potential predictors for postoperative recurrence following subtotal resection. We reviewed the charts of patients who had undergone VS surgery between 1998 and 2007. Thirty patients had an incomplete resection. The principal outcome measure was change in tumor volume (TV) on serial imaging. At a median follow-up of 6.8 years, volumetric measurements showed that 12 patients (40%) developed further tumor growth, while 18 patients remained with stable residual disease. The median rate of growth was 0.53 cm3/year. Two-dimensional measurements confirmed growth in only eight of these patients. The postoperative residual TV correlated significantly with subsequent tumor growth (p = 0.038). All patients with residual volumes in excess of 2.5 cm3 exhibited recurrence. On univariate analysis, only postoperative TV was significantly associated with growth. Median time to failure was 21.5 months. This is the first report of volumetric measurements of VS tumor growth postoperatively. Volumetric measurements appear to be superior to two-dimensional measurements in documenting VS growth and patients with residual tumors >2.5 cm3 have a significantly higher rate of recurrence.
Keywords: vestibular schwannoma; acoustic neuroma; postoperative growth; volumetric measurement; partial resection